The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1158/1541-7786.mcr-06-0227
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Related Receptor α1 Transcriptional Activities Are Regulated in Part via the ErbB2/HER2 Signaling Pathway

Abstract: We previously showed that (a) estrogen-related receptor A1 (ERRA1) down-modulates estrogen receptor (ER) -stimulated transcription in low ErbB2 -expressing MCF-7 mammary carcinoma cells, and (b) ERRA and ErbB2 mRNA levels positively correlate in clinical breast tumors. We show here that ERRA1 represses ERA-mediated activation in MCF-7 cells because it failed to recruit the coactivator glucocorticoid receptor interacting protein 1 (GRIP1) when bound to an estrogen response element. In contrast, ERRA1 activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
106
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 47 publications
4
106
0
Order By: Relevance
“…We have demonstrated that E 2 induction of ERR␣ relies on the MAPK signaling pathway as it is susceptible to a MAPK inhibitor. Stimulation of the MAPK pathway by estrogen can lead to the activation of ERR␣ via phosphorylation (22,78). Phosphorylated ERR␣ binds DNA and interacts with co-activators more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that E 2 induction of ERR␣ relies on the MAPK signaling pathway as it is susceptible to a MAPK inhibitor. Stimulation of the MAPK pathway by estrogen can lead to the activation of ERR␣ via phosphorylation (22,78). Phosphorylated ERR␣ binds DNA and interacts with co-activators more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…MCF-7/WS8 and T47D:A18 human mammary carcinoma cells, clonally selected from their parental counterparts for sensitivity to growth stimulation by E 2 (32), were used in all experiments indicating MCF-7 and T47D cells. Cells were maintained in steroid-replete RPMI 1640, but 3 days before all experiments, were cultured in steroid-free media as previously described (32,33).…”
Section: Methodsmentioning
confidence: 99%
“…33) or ARE(5x)-regulated (pAR-Luc; Panomics) firefly luciferase expression plasmid and co-transfected with a basal TATA promoter-regulated (pTA-srLuc) Renilla luciferase expression plasmid as previously described (33).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA (1 μg) was reversely transcribed with the High Capacity cDNA reverse transcriptase kit (Applied Biosystems) following manufacturer's instructions. The sequences of the primers utilized for real-time qPCR are as follows: tff1 forward primer, 5'-CATC GACGTCCCTCCAGAAGAG-3'; tff1 reverse primer, 5'-CTC TGGGACTAATCACCGTGCTG-3'; 36B4 forward primer, 5'-GTGTTCGACAATGGCAGGCAT-3'; 36B4 reverse primer, 5'-GACACCCTCCAGGAAGCGA-3'; c-myc forward primer, 5'-GCCACGTCTCCACACATCAG-3'; c-myc reverse primer, 5'-TCTTGGCAGCAGGAATAGTCCTT-3'; ebag9 forward primer, 5'-CTGGCAGAGGACGGAAATTA-3'; ebag9 reverse primer, 5'-TCATCCCAGGAAGTCCACTC-3'; the primer sets for egfr and her2 were previously described (36,37). Real-time qPCR was performed using the 7900HT real-time PCR system (Applied Biosystems), the amplicons were detected with SYBR-Green and analysis was performed utilizing the 2 -ΔΔt method (38).…”
Section: Methodsmentioning
confidence: 99%